Cultural fit and subjective well-being on an individual’s intention to migrate - Wong, Charmaine Jiahui (2019)
This study aims to investigate the relationship between cultural fit, subjective well-being, and intentions to migrate. In addition to economic factors of consideration, individuals would also consider affective and cognitive factors in the migration decision-making process. Cultural misfit and subjective well-being were chosen as the two factors of interest that could possibly influence an individual’s intention to migrate. We came up with three hypotheses. Hypothesis 1: The greater the cultural fit between individuals and their country, the lower their intentions to migrate. Hypothesis 2: The higher individuals’ subjective well-being, the lower their intentions to migrate. Hypothesis 3: When subjective well-being is low, the effect of cultural fit on individuals’ intentions to migrate is greater than when subjective well-being is high. Our findings revealed that only Hypothesis 2 was partially supported. Cultural fit and life satisfaction were found to be negatively associated with intentions to migrate, but only life satisfaction was a significant unique predictor of intentions to migrate. This means that individuals with higher life satisfaction would tend to have lower migration intentions. The current study provides a new perspective into the migration decision-making process and demonstrates that there can be situations in which upward social mobility does not apply, such that the social statuses of groups are no longer as important when individuals are faced with low satisfaction with life.